Satirical Magazines Published in Madrid and Barcelona (1875-1910) as Primary Sources for Studying Rural Stereotypes in Secondary Education - Cabañero Martín, Víctor Manuel (Educación y Futuro: Revista de Investigación Aplicada y Experiencias Educativas, 2024)
This article reviews the representation in satirical magazines published in Madrid and Barcelona. To this end, the leading satirical magazines from these cities, published between 1875 and 1906, have been examined. These publications reveal the gradual formation of the male stereotype, a representation that remains consistent with the female stereotype, alongside the per-sistent presence of the era’s prevalent sexist biases—not limited to rural settings but rather presented as cultural traits of these publications-. The study aims to propose a selection of materials for secondary education classrooms featuring images and comedic texts that construct stereotypes of characters, specifically those within a rural context.